Plasmid profiling of multidrug resistant Escherichia coli strains isolated from urinary tract infection patients - Khadgi, Sabin; Timilsina, Uddhav; Shrestha, Basudha (International Journal of Applied Sciences and Biotechnology, 2013)
Introduction- Urinary tract infection is a common community-acquired bacterial disease. Escherichia coli is reported to be the major cause of urinary tract infection. Aim & Objective- The study was conducted with the aim of determining the antibiotic resistance pattern and plasmid profile of multidrug resistant Escherichia coli isolated from Urinary Tract Infection patients. Materials and Method- Antibiotic susceptibility tests were performed against E. coli following the protocol for the Kirby-Bauer disc diffusion method. Plasmid DNA was isolated following the protocol of Kado and Liu. Results- Multidrug resistant isolates exhibited high resistance to drugs like Amoxicillin, Cefixime, Ciprofloxacin, Cotrimethoxazole, Norfloxacin and Ofloxacin. The plasmid profiling showed that all, except one, isolate contained at least one plasmid. A band of approximately 23 kb was seen in most of the isolates. DOI: http://dx.doi.org/10.3126/ijasbt.v1i1.7918 Int J Appl Sci Biotechnol, 2013, Vol. 1(1): 1-4